2015
DOI: 10.3906/kim-1412-64
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the adsorption of a textile dye onto nanoclay using a central composite design

Abstract: Abstract:The main aim of this study was to evaluate the efficacy of montmorillonite clay for the adsorption of C.I. Basic The adsorbent dosage was found to be the key factor that controlled dye adsorption. The adsorption kinetic and isotherm were also investigated. The rate of adsorption showed the best fit with the pseudo-second order model (R 2 = 1). The results of the isotherm study fit the Freundlich model (R 2 > 0.9). The physicochemical properties of the sample were determined by XRF, XRD, FT-IR, and N 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…These numbers indicate that humic acid adsorbed onto bentonite nanoparticles with more power in comparison with nano particles of montmorillonite. Other studies have reported similar results (20,21). According to Figure 5 regression coefficient, the BET isotherm provides a better description for humic acid ad- sorption on montmorillonite than the description that Langmuir and Freundlich isotherms provide for this process (adsorption of humic acid by montmorillonite).…”
Section: Discussionsupporting
confidence: 67%
“…These numbers indicate that humic acid adsorbed onto bentonite nanoparticles with more power in comparison with nano particles of montmorillonite. Other studies have reported similar results (20,21). According to Figure 5 regression coefficient, the BET isotherm provides a better description for humic acid ad- sorption on montmorillonite than the description that Langmuir and Freundlich isotherms provide for this process (adsorption of humic acid by montmorillonite).…”
Section: Discussionsupporting
confidence: 67%
“…Biological treatments are not sufficiently to adsorbed organic dyes and delight colored wastewaters due to the low biodegradability of organic dyes. Therefore, physicochemical processes have been used to degrade or remove organic dyes in aqueous solutions [13,14]. Adsorption using solid adsorbent is one of the physicochemical treatment approaches, and has been established to be efficient and economical [14].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, physicochemical processes have been used to degrade or remove organic dyes in aqueous solutions [13,14]. Adsorption using solid adsorbent is one of the physicochemical treatment approaches, and has been established to be efficient and economical [14]. In spite of, activated carbon was the most widely adsorbent employed but it has been limited due to its high capital and operative costs [11,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…36 The goodness-of-fit of the model is checked by using an R 2 value of 0.9331 and means that approximately 93% of the data were compatible and 7% of the variance could not be explained by the model. 32,34 R 2 adj shows the degree of correlation between the experimental and predicted values 34,37 and also summarizes the model adequacy and fitness and serves to correct R 2 values for the sample size and the number of terms. 32 As values near 1 are acceptable, 32 an R 2 adj value of 0.8706 shows the proper significance of the model.…”
Section: Optimization Using Rsm Methodologymentioning
confidence: 99%